The Effect of Roundhouse Stagey On Cognitive Achievement and Retention In Methods of Teaching Physical Education and Attitude Improvement Towards it In Physical education College Students - Kamal-Al Deen, Muayad (Journal of Physical Education, 2019)
The problem of the research lies in answering the following question: what is the effect of roundhouse strategy on academic achievement and retention in methods of teaching class and improving students’ attitudes towards this strategy. The researcher aim at identifying the effect of this strategy on academic achievement and retention in teaching method class as well as improving the students of physical education and sport sciences college attitudes towards it. The researcher used the experimental method. The subjects were (60) students divided into controlling and experimental groups. The researcher used academic achievement test prepared by Mulla Abiada as well as attitudes towards methods of teaching scale. He concluded that roundhouse strategy surpassed the traditional style followed in teaching thirds Year College of physical education and sport sciences’ students in methods of teaching class.